Self-efficacy and Performance of Military Police Soldiers - Bassalo, Fabrício Silva (2020)
The theme about police training in Brazil has taken place in discussions about new models of public security and an adequate professional profile for executive police activity. In this matter, we sought to evaluate the perception of performance of self-efficacy in the training of soldiers of the Military Police. A field research was conducted in a survey in order to know specific aspects of personal perception. A total of 284 graduates from 2018/2019 class participated. The results showed that 63% participants are above the level of education required by the contest. Regarding the evaluation of the course, according to their perception, the grades with the highest expression were 1 (0.4%) and 8.0 (33.2%). Considering the training for police inquire skills and the ability to interact with justice agencies, 75.6% have completed higher education, 70.8% have incomplete higher education and 55.2% have high school, which answered feeling capable for this item, corroborating the idea that they have levels of self-efficacy. It is suggested that future studies may encompass new training hubs in order to understand other regions.